2018
DOI: 10.5812/pedinfect.57071
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ascorbic Acid Supplementation in Relief of Symptoms Due to Febrile Upper Urinary Tract Infection in Children, a Clinical Trial and Hospital Based Study

Abstract: Background: Urinary tract infections (UTIs) as a urological disorder occur in 1% -3% of females and 1% of males. This disease can induce severe complications such as pyelonephritis. Objectives: The current study aimed at evaluating the efficacy of vitamin C supplementation on UTI in children. Methods: The current clinical trial was conducted on 152 female children with UTI admitted to Amir-Kabir hospital, Arak, Iran. The cases were randomly divided, based on blocked groups, into two treatment and control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Ascorbic acid supplementation as a possible tool to relieve UTI symptoms in children has been evaluated. One clinical trial included 152 female children who tested positive for UTI in a hospital setting and were assigned to either an ascorbic acid supplemented treatment group or a placebo control ( Yousefichaijan et al, 2018 ). These pediatric patients were also given routine parenteral ceftriaxone for admitted patients followed by oral cefixime antibiotics following patient discharge in conjunction with ascorbic acid or placebo.…”
Section: Complementary Medicine For Treating Urinary Tract Infections...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ascorbic acid supplementation as a possible tool to relieve UTI symptoms in children has been evaluated. One clinical trial included 152 female children who tested positive for UTI in a hospital setting and were assigned to either an ascorbic acid supplemented treatment group or a placebo control ( Yousefichaijan et al, 2018 ). These pediatric patients were also given routine parenteral ceftriaxone for admitted patients followed by oral cefixime antibiotics following patient discharge in conjunction with ascorbic acid or placebo.…”
Section: Complementary Medicine For Treating Urinary Tract Infections...mentioning
confidence: 99%
“…These pediatric patients were also given routine parenteral ceftriaxone for admitted patients followed by oral cefixime antibiotics following patient discharge in conjunction with ascorbic acid or placebo. The trial found that ascorbic acid supplementation resulted in controlled symptoms associated with UTIs, including fever, dysuria, urinary urgency, and dribbling urine with decreased frequency of these symptoms in the treatment group ( Yousefichaijan et al, 2018 ). These results suggest that ascorbic acid plays a role in reducing UTI symptoms among pediatric females when given intravenous and oral antibiotics; however, additional exploration is needed to confirm these results.…”
Section: Complementary Medicine For Treating Urinary Tract Infections...mentioning
confidence: 99%
“…Yousefichaijan et al studied the efficacy of vitamin C supplementation on UTI in children for 14 days. The results showed that vitamin C supplementation was able to control the symptoms of UTI, including dysuria, fever, urinary urgency, and also dribbling urine [59]. Ochoa et al investigated the role of a daily intake of vitamin C for its effect on UTIs during pregnancy.…”
Section: Vitaminsmentioning
confidence: 99%
“…Ascorbic acid (AA) is often recommended as a prophylactic agent for prevention of recurrent urinary tract infections. Research on the effectiveness of AA supplementation has been carried out on diverse groups including healthy volunteers [ 13 ], pregnant women [ 14 ], children with febrile upper urinary tract infection [ 15 ], spinal cord injury patients [ 16 ], calcium-stone-forming patients [ 17 ], and kidney transplant patients [ 18 ]. The published results are contradictory.…”
Section: Introductionmentioning
confidence: 99%